Workplace experiences and career advancement prospects for women in the hotel industry in India - Hussain, Sarah; Soni, Gagandeep; Harkison, Tracy; DeMicco, Frederick (Turyzm/Tourism, 2024)
This study aims to provide an insight into the factors that affect workplace experiences and opportunities for career progression of female employees in the Indian hotel industry. It provides a much-needed perspective on the work-life of women in the Indian hotel industry. The study had two phases: a systematic literature review was conducted for the first phase and the second phase included conducting semi-structured in-depth interviews. The findings of this study reveal that working in the hotel industry remains an ultimate choice for women where they have the opportunities to connect and socialize, enjoy and learn amidst the various challenges and barriers faced. The issue of gender is irrelevant for the women who set their standards and want to achieve their goals. Women show resilience and work against all odds with self-motivation to reach these goals.